The Minimum Involvement of People with Aphasia in the Creation of Quality-of-Life Questionnaires - Charalambous, Marina; Kambanaros, Maria; Jean Marie, Annoni (My University, 2021)
Background and Aims There is a large body of literature on the use of questionnaires to describe the impact of aphasia on stroke survivors’ quality of life (QOL). The findings demonstrate robust evidence for the severe effects of communication deficits on social integration and well-being for people with aphasia (PWA) post stroke. Traditionally, PWA are excluded as research partners, because of perceived barriers in communication. As a result, there is potentially a gap between the factors chosen in the tools and the pragmatic needs of PWA. The purpose of this study is to explore the presence vs. the absence of PWA after stroke in the creation of QOL and aphasia impact-related questionnaires (AIR-Qs). Methods A scoping review was conducted by an expert librarian in health sciences and two independent reviewers based on the PRISMA-ScR protocol. Search strings were based on Mesh terms and keywords associated with the term ‘stroke’, ‘people with aphasia’, ‘communication’, ‘well- being’, and ‘quality of life’. Five databases were used: Medline Complete, PubMed, PsychINFO, Scopus, and Google Scholar. Results Out of 952 results, 20 studies met the eligibility criteria. Out of these, only 4 AIR-Qs studies (20%) were reporting the direct involvement of PWA. No QOL tools reported direct involvement. Conclusions There is a lack of a research framework that will promote consistency and transparency in reporting the involvement of PWA after Stroke in qualitative participatory studies. The absence of such a framework limits the effectiveness to promote equitable best practice in stroke aphasia rehabilitation.
Keywords: Stroke; Patient and Public Involvement; Quality of Life Questionnaires